Increasing the uptake of electronic prescribing in primary care. Issue 1 (25th May 2017) - Imambaccus, Nazia; Glace, Samuel; Heath, Rory
Abstract : Electronic prescribing is a form of paperless prescribing that is reported to reduce prescription mistakes and increases the cost effectiveness of the process. In England, around 1.5 million prescriptions are generated in general practice daily. Thus by reducing costs and increasing efficiency of this system through electronic prescribing, costs can be driven down. In this Quality Improvement project, a GP practice in London with approximately 3000 patients on record was assessed for its electronic prescribing rates throughout 3 intervention cycles over a period of 2 months. A baseline value of how many patients were already assigned to electronic prescribing was obtained and a period of normal change over a fortnight without any intervention was also assessed (an increase in 15 patients). These values were then used to illustrate any benefits of the interventions completed during the intervention cycles. An introduction of a new electronic prescribing form saw fortnightly uptake rates increase by 20%. The addition of leaflets and posters in the practice produced a decrease of 26% in fortnightly uptake rate. The final intervention included a staff meeting, computer notes to remind staff of electronic prescribing and attaching the new forms to paper prescriptions. This saw an increase in rates of 80% over two weeks. Overall, this project has illustrated that information provision of electronic prescribing needs to be more than just forms or posters. Indeed, the most effective way of improving rates relies on having a driven and motivated staff who are themselves well informed on electronic prescribing alongside adequate information placement for patients to access.